Happiness, Morality, Rationality, and Challenges in Implementing Smart Government Policy. (4th May 2018) - Yaghi, Abdulfattah; Al-Jenaibi, Badreya
Abstract : Smart government is a public policy that aims to improve people's happiness by utilizing information communication technology (ICT) in providing public services. The present article explores the perceptions of public sector managers about the state of smart government within their agencies. Thematic analysis of 34 in-depth interviews reveals that the policy is successful and the managers perceive smart government as relevant to good governance. Implementation of the policy seems to be driven by a combination of moral values (principles, duty, and virtues) and rational interests (public, personal, professional, organizational, and legal). Moreover, the managers indicate that smart government contributes to making people happy, and that the policy improves not only public sector services but also the relationship between people and the government. Although the policy is successful, moral, and rational, some challenges may exist.